Laparoscopic Splenectomy for Splenic Hamartoma: A Case Report. (22nd October 2012) - Pisani Ceretti, Andrea; Bislenghi, Gabriele; Virdis, Matteo; Maroni, Nirvana; Gatti, Andrea; Opocher, Enrico
Abstract : Hamartoma is a rare splenic benign tumor usually accidentally detected as a radiologic finding. Preoperative diagnosis poses a challenge and thus surgery becomes necessary to confirm the clinical suspicion. Laparoscopic splenectomy has gained consensus as a standard surgical procedure particularly for autoimmune hematological diseases. This former experience has allowed this technique to be extended to other splenic pathologies. Here we report a case of total laparoscopic splenectomy for a bulky splenic hamartoma in a young male patient.